Potential, impact and sustainable approach of fishing tourism in Kenyir Lake / Mohd Ariff Alias - Alias, Mohd Ariff (2013)
Changing trends in travel pattern, recreational and adventure tourism which consist of various enjoyable activities are rapidly growing and becoming more popular. As such, Malaysia is promoting fishing activities as one of the divisions under recreational tourism due to the vast potential and selection of fishing locale which have diverse species of fish in accordance with the equatorial climate of the country. This study aimed to explore the potential, impact of developments and the sustainable approach that have been implemented in order to preserve the natural resources as well as maintaining the numbers of incoming visitors to Kenyir Lake. Qualitative approach with semi-structured interview with fishing experts was undertaken to get valid data on the development and sustainable strategies that have been executed at the research area. Findings clearly revealed that, fishing tourism has a big potential to attract more tourists to the country and there are identical data on the positive and negative impacts of the development within the Kenyir Lake area. There are many strategies being implemented by Central Terengganu Development Authorities (KETENGAH) and Malaysia Fishing Association (PeMM) together with knowledgeable anglers who strive to preserve Kenyir Lake for future generations to come.